2016
DOI: 10.1007/s00426-016-0755-4
|View full text |Cite
|
Sign up to set email alerts
|

Embodied perspective-taking indicated by selective disruption from aberrant self motion

Abstract: Spatial perspective-taking that involves imagined changes in one’s spatial orientation is facilitated by vestibular stimulation inducing a congruent sensation of self-motion. We examined further the role of vestibular resources in perspective-taking by evaluating whether aberrant and conflicting vestibular stimulation impaired perspective-taking performance. Participants (N = 39) undertook either an “own body transformation” (OBT) task, requiring speeded spatial judgments made from the perspective of a schemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Somatosensory information from holding heavy bags might reduce the discrepancy between the actual and imagined rotation of objects. This explanation is consistent with previous findings that imagined movement is facilitated or impaired by the presence of congruent or incongruent sensorimotor input, respectively (e.g., Gardner et al, 2017;Kunz et al, 2009;van Elk & Blanke, 2014). Beyond previous findings, the present study also reported a case where somatosensory inputs from the hands, without movement, could modulate mental rotation processing.…”
Section: Discussionsupporting
confidence: 93%
“…Somatosensory information from holding heavy bags might reduce the discrepancy between the actual and imagined rotation of objects. This explanation is consistent with previous findings that imagined movement is facilitated or impaired by the presence of congruent or incongruent sensorimotor input, respectively (e.g., Gardner et al, 2017;Kunz et al, 2009;van Elk & Blanke, 2014). Beyond previous findings, the present study also reported a case where somatosensory inputs from the hands, without movement, could modulate mental rotation processing.…”
Section: Discussionsupporting
confidence: 93%
“…This spontaneous tendency to adopt another agent’s perspective has been largely replicated (Conson et al., 2017; Furlanetto et al., 2013; Todd et al., 2011). At the psychological level, it is suggested that the occurrence of such a social phenomenon involves representing one’s own body as in the physical location of the other person (e.g., Gardner et al., 2017; Kessler & Rutherford, 2010; Kessler & Thomson, 2010; Michelon & Zacks, 2006; Surtees et al., 2013). By doing so, humans would be able to anticipate others’ behaviors, which would facilitate upcoming social interactions (Freundlieb et al., 2016).…”
mentioning
confidence: 99%
“…Since embodiment is related to the experience of one’s own body in the first-person perspective, changing perspective by mentally rotating the body image in order to judge whether it matches a visually presented figurine is challenging. Indeed, complex body-related mechanisms are required ( Blanke, 2005 ; Kaltner et al, 2014 ; van Elk and Blanke, 2014 ), such as flexible control of self-perspective-taking and disembodiment ( Arzy et al, 2007 ), and alignment of somatosensory and vestibular information ( Zacks et al, 1999 ; van Elk and Blanke, 2014 ; Gardner et al, 2017 ). Therefore, better performance in the OBT task (i.e., shorter RT and higher accuracy) suggests that changing self-perspective and disembodying is achieved more easily.…”
Section: Discussionmentioning
confidence: 99%
“…Since the correlation between OBT task performance and SPS perception was not perfect, the present experiment does not allow us to draw conclusions as to which of the processes involved in the OBT task determine the perception of SPS, or even to what degree. For instance, processes of spatial mental manipulation, attention, and simulation of sensory and vestibular information have been advanced as determinants of the ability to align one’s own body orientation to that of a third party and to perspective-taking ( Gardner et al, 2017 , 2018 ; Pesimena et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%